Evaluation of Implementation of Independent Curriculum (Kurikulum Merdeka) - Reffy Ananda Rizki; Lulu Fahkrunisa (Journal of Curriculum and Pedagogic Studies (JCPS), 2022)
Pandemic COVID -19 brings many influences in our life, including educational system in Indonesia. The students experienced learning loss and learning gap during pandemic. Without any solution, the education in Indonesia can be left behind. Therefore, The Minister of Education and Culture revised the national curriculum. This curriculum will be used as recovery of educational crisis because of Pandemic. This curriculum is Kurikulum Merdeka or Independent Curriculum. This curriculum has not been fully implemented in nationwide until 2024. However, the preparation of this curriculum is on progress. The school can apply Implementasi Kurikulum Merdeka or Implementation of Independent Curriculum. This aim of this study was to evaluate the implementation of this curriculum through analysing related document such educational system law, regulation of the Minister of Education and Culture, article, and journal. Based on analysis, the result showed that implementation of new curriculum has both challenges and positive impact. The main challenge is related to the readiness of the teacher while the main positive impact is there is improvement in terms of communication, collaboration, critical thinking, and creative thinking of the students. The result of this study can be used as consideration in formulating educational policy, reflection for the teachers, principal and other stakeholders